دور مستشار التوجيه والارشاد المدرسي والمهني في الحد من المشكلات السلوكية العنف والتنمرالمدرسي - دريهم إسلام; صحراوي جهاد (University Of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة إلى الكشف عن دور مستشار التوجيه والإرشاد المدرسي والمهني في التخفيف من مشكلة العنف والتنمر المدرسي، ولهذا الغرض انطلقت الدراسة من الفرضيات التالية: -يساهم مستشار التوجيه والإرشاد المدرسي والمهني في الحد من مشكلة العنف في الوسط المدرسي. -يساهم مستشار التوجيه والإرشاد المدرسي والمهني في الحد من مشكلة التنمر في الوسط المدرسي. ولقد إعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي نظرا لتماشيه مع موضع الدراسة في حين تمثلت عينة الدراسة في مستشاري التوجيه والإرشاد المدرسي والتي كان عددها (30) مستشارا وللحصول على المعلومات والبيانات تم الإستعانة بأداة الإستبيان والتي تتضمن (24) بندا. ولقد توصلت الدراسة إلى النتائج التالية -أن مستشار التوجيه والإرشاد المدرسي والمهني يساهم بشكل إجابي في الحد من مشكلة العنف المدرسي في الوسط المدرسي. - أن مستشار التوجيه والإرشاد المدرسي والمهني يساهم بشكل إجابي في الحد من مشكلة التنمر المدرسي في الوسط المدرسي. This study aimed to reveal the role of the school guidance and vocational guidance counselor in alleviating the problem of school violence and bullying. For this purpose, the study started from the following hypotheses: -The school and vocational guidance and counseling counselor contributes to reducing the problem of vIolence in the school environment. -The school and vocational guidance and counseling counselor contributes to reducing the problem of bullying in the school environment. In this study, we relied on the descriptIve analytical approach due to its consistency with the subject of the study, while the study sample represented school guidance and counseling counselors, the number of which was (30), and to obtain information and data, the questionnaire tool was used, which includes (24) items. The study reached the following results -The school and vocational guidance and guidance counselor contributes positively to reducing the problem of school violence in the school environment. -The school and vocational guidance and guidance counselor contributes positively to reducing the problem of school bullying in the school environment.
دراسة ميدانية بمتوسطات وثانويات الوادي
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: مستشار التوجيه; Conseiller d'orientation; Guidance Counselor; المشكلات السلوكية; Problèmes de comportement; Behavioral problems; العنف المدرسي; Violence à l'école; School violence; التنمر المدرسي; L'intimidation à l'école; School bullying